Pemilihan komponen dan pembuatan alat destilasi minyak sereh dengan kapasitas 10 kg - Ifan; Lazuardy, Dedi; Djoko Yudisworo, W. (Universitas Majalengka, 2024)
This research aims to design and manufacture a citronella oil distillation device with a capacity of 10 kg. The component selection process involves analysis of various factors such as efficiency, cost, material availability, and ease of maintenance. The main components selected include extraction tubes, condensers and heating systems. Choosing the right material, such as stainless steel for corrosion resistance, is one of the main focuses to ensure tool durability. The design of this distillation tool takes into account aspects of ergonomics and user safety. The manufacturing process involves several stages, starting from detailed design, material procurement, to assembling and testing the equipment. The test results show that this distillation equipment is capable of producing lemongrass oil with quality that meets standards, as well as better time efficiency compared to traditional methods. Thus, it is hoped that this distillation equipment can increase lemongrass oil production, especially for farmers and small and medium industries.